EFFECT OF CU AS МINORITY АLLOYING ЕLEMENT ON GLASS FORMING ABILITY AND CRYSTALLIZATION BEHAVIOR OF RAPIDLY SOLIDIFIED AL-SI-NI RIBBONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The influence of copper as a minority alloying element in the process of rapid solidification of Al-Si-Ni ribbons produced by Chill Block Melt Spinning (CBMS) was investigated. XRD and TEM analyses proved a completely amorphous structure of the alloys Al74Ni16Si10 and (Al74Ni16Si10)98Cu2. The crystallization behaviour of these alloys was studied by DSC analysis. It was found that the crystallization of the amorphous alloys (Al74Ni16Si10)100-xCux, x=0, 2 runs in two steps. The temperatures Tx1 and Tx2 of each of the crystallization steps were determined. It was proven that the addition of 2 at. % copper does not significantly change Tx temperatures. The temperature difference ΔTx was calculated and it showed that more thermally stable is the copper containing alloy. Crystalline analogues of the amorphous alloys were obtained by annealing of the melt-spun amorphous ribbons at a temperature which exceeded by 170°C the onset crystallization temperature. The type and size of separated crystalline phases were determined by XRD. It was found that the addition of 2 at. % Cu to Al74Ni16Si10 alloy causes a separation of new phases - Cu3.8Ni and (Al, Cu)Ni3 and 54%, 24% and 7% size increase of the phases Al, Al3Ni, NiSi2 respectively.